Pollution : examining cause and effect relationships - Anderson, Bob; Buggey, JoAnne (San Diego, CA : Greenhaven Press, 1992)
Presents opposing viewpoints on pollution and its effects on the atmosphere, water, and people of the planet.
Keywords: Pollution; Pollution; Critical thinking